Communication privacy management in college athletics: Exploring privacy dilemmas in the athletic/academic advisor student-athlete interpersonal relationship - Jason Thompson (Journal of Applied Sports Management, 2011)
The purpose of the present study was to explore how athletic/academic advisors communicatively managed privacy boundaries with college student-athletes. The researcher interviewed 37 athletic/academic advisors to address one central research question: What type of dilemmas do athletic/academic advisors experience when managing the privacy boundary surrounding student-athletes’ private information? Athletic/academic advisors who were interviewed represented 21 different institutions of four different NCAA division levels (i.e., I, IAA, II, and III), and more than 10 separate NCAA athletic conferences. Findings indicated that athletic/academic advisors experienced different types of dilemmas which revolved around private information student-athletes disclosed regarding academic, athletic, and personal issues. This research presents specific dilemmas advisors experienced. Practical applications as well as directions for future research are also discussed.
Keywords: Privacy Boundary; Academic Advising; College Student- Athletes; Athletic/Academic Advisors; Communication Privacy Management theory